The Role of AI in Education Management Information Systems in Indonesia - Zabrina Elvaretta; Nisrina Rosyada; Ika Hafsah Faunia Zazillah; Aisyah Fitriani; Agnia Azka Nabilla; Hestina Amelia; Zahrotul Milatina; Naeza Fara Diba; Nabilatul Fauziyah; Muhammad Irwan; Mansur Chadi Mursid (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the role of artificial intelligence (AI) in management information systems (MIS) in the Indonesian education sector, focusing on its opportunities, challenges, and implications for learning quality. The rapid advancement of AI technology has significantly changed the way educational institutions manage information, support decision-making, and improve the teaching and learning process. This research aims to provide a comprehensive understanding of the integration of AI in MIS education and its impact on the quality of education. The study uses a literature review method by analyzing the latest scientific publications related to AI in education and information systems. Relevant articles are systematically selected, reviewed, and synthesized to identify key themes, including the role of AI, its potential benefits, implementation challenges, and its impact on learning outcomes. These findings reveal that AI contributes to improving efficiency in academic management, enabling personalized learning experiences, and supporting data-driven decision-making in educational institutions. Additionally, AI improves student engagement and learning outcomes through a more interactive and adaptive learning environment. However, some challenges remain, including limited digital literacy, inadequate infrastructure, ethical issues, data privacy issues, and uneven access to technology. In conclusion, AI has a strong potential to improve the effectiveness of management information systems in education. Nevertheless, its successful implementation depends on proper management, institutional support, clear policies, and the readiness of users to adopt and utilize technology responsibly.